Propagation of Syndesmotic Injuries During Forced External Rotation in Flexed Cadaveric Ankles. Issue 6 (25th June 2018) - Mait, Alexander Ritz; Forman, Jason Lee; Nie, Bingbing; Donlon, John Paul; Mane, Adwait; Forghani, Ali Reza; Anderson, Robert B.; Cooper, M. Truitt; Kent, Richard W.
Background: Forced external rotation of the foot is a mechanism of ankle injuries. Clinical observations include combinations of ligament and osseous injuries, with unclear links between causation and injury patterns. By observing the propagation sequence of ankle injuries during controlled experiments, insight necessary to understand risk factors and potential mitigation measures may be gained. Hypothesis: Ankle flexion will alter the propagation sequence of ankle injuries during forced external rotation of the foot. Study Design: Controlled laboratory study. Methods: Matched-pair lower limbs from 9 male cadaveric specimens (mean age, 47.0 ± 11.3 years; mean height, 178.1 ± 5.9 cm; mean weight, 94.4 ± 30.9 kg) were disarticulated at the knee. Specimens were mounted in a test device with the proximal tibia fixed, the fibula unconstrained, and foot translation permitted. After adjusting the initial ankle position (neutral, n = 9; dorsiflexed, n = 4; plantar flexed, n = 4) and applying a compressive preload to the tibia, external rotation was applied by rotating the tibia internally while either lubricated anteromedial and posterolateral plates or calcaneal fixation constrained foot rotation. The timing of osteoligamentous injuries was determined from acoustic sensors, strain gauges, force/moment readings, and 3-dimensional bony kinematics. Posttest necropsies were performed to document injury patterns. Results: A syndesmotic injury was observed in 5 of 9 (56%) specimens tested in a neutral initial posture, in 100% of the dorsiflexed specimens, and in none of the plantar flexed specimens. Superficial deltoid injuries were observed in all test modes. Conclusion: Plantar flexion decreased and dorsiflexion increased the incidence of syndesmotic injuries compared with neutral matched-pair ankles. Injury propagation was not identical in all ankles that sustained a syndesmotic injury, but a characteristic sequence initiated with injuries to the medial ligaments, particularly the superficial deltoid, followed by the propagation of injuries to either the syndesmotic or lateral ligaments (depending on ankle flexion), and finally to the interosseous membrane or the fibula. Clinical Relevance: Superficial deltoid injuries may occur in any case of hyper–external rotation of the foot. A syndesmotic ankle injury is often concomitant with a superficial deltoid injury; however, based on the research detailed herein, a deep deltoid injury is then concomitant with a syndesmotic injury or offloads the syndesmosis altogether. A syndesmotic ankle injury more often occurs when external rotation is applied to a neutral or dorsiflexed ankle. Plantar flexion may shift the injury to other ankle ligaments, specifically lateral ligaments.